Analysis of Employee Job Satisfaction Based on the Roles of Job Enlargement, Cognitive Crafting, and Motivation - Lumbantoruan, Pandaraman; Khairani, Cut; Setiani, Made Yudhi (Manunggal Halim Jaya, 2026)
This study employs a mixed-method approach with an explanatory sequential design (QUAN→qual) to analyze the influence of job enlargement, cognitive crafting, and motivation on team member job satisfaction at the Regional Office of the Directorate General of Treasury of Aceh Province, in the context of implementing TREFA (Treasurer, Regional Chief Economist, and Financial Advisor) and shadow organization. The quantitative phase was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) on 47 employees divided into two clusters: 21 officials and 26 staff members. The qualitative phase was carried out through in-depth interviews with 11 key informants. The findings reveal a significant hierarchical disparity. Job enlargement positively affected officials (T-statistic = 2.871) but not staff members (T-statistic = 0.701). Cognitive crafting did not show a significant effect, although employees applied gamification and goal framing strategies. Motivation demonstrated a positive and significant effect at all levels (T-statistic = 3.158), with the highest path coefficient. The combined analysis identified three main phenomena: the Hierarchy-Differentiated Job Design Effect, the Cognitive Crafting Paradox, and Universal Public Service Motivation. The three variables had a significant influence with a coefficient of determination of 53.1%, although their contributions varied. This study contributes to developing Contextual Job Design Theory for the public sector and the Bounded Cognitive Crafting Model. It provides recommendations for implementing TREFA that are more aligned with the hierarchical characteristics of employees in the public sector.